Attribution of stratospheric ozone change and associated climate impacts - Bandoro, Justin (Massachusetts Institute of Technology, 2018)
Thesis: Ph. D. in Climate Science, Massachusetts Institute of Technology, Department of Earth, Atmospheric, and Planetary Sciences, 2018. Cataloged from PDF version of thesis. Includes bibliographical references. Recognition of stratospheric ozone depletion as a significant global danger sparked the landmark international agreement of the Montreal Protocol to control the production of ozone depleting substances (ODSs). There are now signs of stratospheric ozone recovery, and it is essential to understand whether the observed historical changes, during both the depletion and recovery eras, are directly the result of secular changes in ODSs, or influenced by other anthropogenic and natural forcings such as greenhouse gases (GHGs) and solar variability. This thesis explores the climate impacts of stratospheric ozone depletion, and how we can attribute, with high confidence, the causes of observed changes in stratospheric ozone. First, the linkages between Antarctic ozone loss and midlatitude surface climate changes are investigated. Unusually hot summer extremes in Australia, South America and Africa were found to be associated with elevated levels of ozone the previous November, and that this link has only emerged in the era of the Antarctic ozone hole. This study provides motivation for understanding the causes of ozone changes, showing direct impacts to regions where humans live. Second, a formal detection and attribution study of stratospheric ozone change is presented. A multi-satellite observational dataset and simulations from a chemistry climate model are analyzed. An improvement to conventional fingerprint attribution methodology is presented that accounts for nonlinearities in the temporal evolution of anthropogenic forcings. High confidence in the detection of ODSs upon observed stratospheric ozone change is shown. Detection of a GHG signal, in stratospheric ozone, is projected to emerge in the mid-21st century. Third, the improved attribution methodology is applied to seasonal atmospheric ...